Penegakan Hukum Terhadap Pengusaha Rokok Tanpa Peringatan Kesehatan Di Kota Pekanbaru Berdasarkan Undang-Undang Nomor 36 Tahun 2009 Tentang Kesehatan - Chandra, Billy Danio; Deliana, Evi; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Cigarettes become a business that always involves between national borders. Cigarettes also become a big need in the Republic of Indonesia, because consumers and lovers of cigarettes in Indonesia are very high. Cigarettes today are not only known in the form of bars but also in the form of e-cigarettes or often called vapors. In Indonesia cigarettes are no longer foreign objects for consumption, but have become a habit for people to consume cigarettes. Cigarettes are usually sold in box packages or paper packages that can be easily inserted into the pocket. The packages are also generally accompanied by health warnings that warn of the health hazards that can be caused by smoking, such as lung cancer, heart attacks. Arrangement of cigarette packs has been regulated in Law Number 36 of 2009 concerning Health. But in fact there are still many circulating packaged cigarettes that does not have the danger of health warnings in the form of images or writing. This act is prohibited and included in a crime which has been regulated in Law Number 36 of 2009 concerning Health. The problems and objectives that will be discussed in this thesis are to find out how law enforcement is applied to cigarette entrepreneurs without health warnings in Pekanbaru City based on Law Number 36 of 2009 concerning Health.This type of research is sociological, because in this study the author immediately conducted research on the location or place under study in order to provide a complete and clear problem under study. This research was conducted at the Food and Drug Supervisory Agency of Riau Province, Pekanbaru City Police Department and the shop selling cigarettes without health warnings circulating in Pekanbaru, while the population and samples were all parties related to the problems examined in this study, the data sources used, primary data and secondary data, data collection techniques in this study with interviews, questionnaires and literature studies.The results of the study can be concluded that Law Enforcement of cigarette entrepreneurs without health warnings in the form of images in the city of Pekanbaru itself has not gone well and maximally. The constraints faced caused this law enforcement to circulate cigarettes without warning to be low and difficult to implement optimally. To overcome this problem, it is advisable to tighten supervision of cigarette breeding without warning and also provide socialization to the public so that people understand more about the rules of selling cigarettes without warning labels.Kata kunci : Law Enforcement - Cigarettes – Health Warnings - Health Law